Integration of Religious Moderation Values in Education at Islamic Boarding Schools: Building a Tolerant and Islamic Generation (EDUKASIA, 2024)
Indonesia education system applied at Islamic boarding schools is functioning as a medium for instilling the values of religious moderation. This methodological framework is to cultivate a generation who has those certain characters, inclusiveness, appreciation of diversity, and the capacity to coexist harmoniously in a pluralistic society. The assimilation of religious moderation values at Islamic boarding schools is reflected in formal education and informal activities as well as daily practices to equip students with tolerance, equality and a firm commitment to the national values. This study used a qualitative methodology equipped with a descriptive-analytic framework, utilizing data collection techniques such as in-depth interviews, observations, and document analysis. The research findings could be drawn in three main conclusions. First, the application of formal and informal education strategies in the Islamic boarding school environment has included moderation (tawasuth), equality (musawamah), balance (tawazun), justice ('adl), and tolerance (tasamuh). Second, the implementation has been done through pedagogical methods, extracurricular involvement, and flag ceremonies. The research implications could be observed in students' moderate attitudes and behavior, such as four important indicators: devotion to the nation, tolerance, rejection of violence, and acceptance of cultural norms.